DIGITAL PAYMENT AS A KEY ENABLER OF E-GOVERNMENT SERVICES: A CASE STUDY OF CHANDIGARH CITY (INDIA) - et al., Manjul Vaidya (International Journal of Control and Automation, 2020)
Going digital has been one of the primary priorities of Govt. of India. The study is limited to Chandigarh City. The research is primarily focussed on evaluating citizens awareness, perception and concerns about the adoption of digital payment system in the domain of e-government services. Primary data is collected and empirically tested. The study also focussed on role of govt in reinforcing digital modes by Chandigarh citizens It has been observed that digital payment space is been increasingly occupied by non-traditional players offering next generation products and services. Citizens services are focussed in the research. The study found that e-sampark centers are very active in city. Study found that people prefer digital payments over traditional ways because of convenience primarily. MSampark needs to be strengthened. Connectivity of mobile phones and other related infrastructure need to be worked upon for smooth implementation of digital payments. Study found that city has lot of potential for successful implementation of Digital payment and receipt platform being availability of more young and educated population in the city. The study concluded that age, education and profession have significant impact over awareness and usage of digital payment platform in Chandigarh City.